P285 Longitudinal single cell transcription profiling of peripheral blood disentangles shared and biologic-specific patterns of early remission in active IBD patients. (21st January 2022) - Bernardes, J P; Mishra, N; Schulte-Schrepping, J; Herresthal, S; Tran, F; Aden, K; Beyer, M; Schultze, J; Rosenstiel, P
Abstract: Background: IBD patients suffer from an uncertain disease course with only 10–20% of patients sustainably benefiting from complete and long-term remission, despite several modern biologic therapies being available. Large multi-omics datasets aimed to elucidate the relationship between changes in disease pathophysiology upon introduction of targeted therapy have delineated overal molecular pathways affected by biologic treatment (e.g. anti-TNF treatment). However, cell-specific molecular studies with the ability to detect cellular features associated with biologic treatment remain scarce, in particular, studies that focused on the mechanisms of action different biologic treatments and potential predictors of early therapy response. Methods: We collected longitudinal single-cell RNA-seq data from 21 IBD patients treated with anti-TNF and anti-IL12/23 biologic treatments. The analysis included single-cell transcription profiles of PBMCs (>500, 000 cells) collected before and two and six weeks after the first round of treatments. Cell-types of interest were identified by selecting changes in immune cell proportions and molecular patterns detected throughout the course of treatment. Specifically, we were interested in identifying molecular pathways that distinguish patients undergoing remission at 14 weeks of treatment (Partial Mayo score <2 or HBI <5). Results: Upon anti-TNF therapy, most patients displayed an increase in the number of B cells, with patients with a favourable disease outcome most likely to display an increase in the proportion of memory and transitional B cells. Remarkably, for Crohn's disease patients, transitional B cell proportion increased throughout the course of anti-TNF treatment, while it decreased for patients undergoing anti-IL12/23 treatment. Molecular signatures related to leukocyte and lymphocyte proliferation were shared at early time points of therapy response, but interestingly, the decrease was not sustained for patients not undergoing remission. Similar patterns could be identified for NF-κB and Toll-like receptor signaling pathways in memory B cells. Moreover, we identified a molecular cluster comprised of Fc receptor-like (FCRL) family members that might infer response to anti-TNF treatment even before the treatment has started, implying hyperactivity of B cells in inflammation as a determinant factor of therapy response. Conclusion: Here, we identified cell-type specific molecular changes in the B cell compartment that are specific to the biologic treatment. Underlining the importance of comparative clinical studies in boosting the rates of patients with a high chance for long-term benefit, by stringent optimization of therapy and personalized treatment.